Phenomenological Study of the Use of Discord Application as a Medium of Da’wah Communication to the Salam Talk Community - Fita Fathurokhmah; Andini Patria Damayanti (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
Da'wah, that is happening today, is no longer centered on the pulpit. One of the phenomena carried out in the newest application is Discord, which game players widely use for preaching in a modern way through an existing community, namely